Math seems like a tough prospect to students simply because they have no idea what all those symbols and seemingly random letters mean. Not everyone can keep up with the teacher in class and since leaning math out of a textbook is not really possible, this leaves a lot of frustrated students who are convinced that math is a difficult subject. It doesn't have to be that way if you use online, live math help which will help you improve your grades and learn to enjoy the subject. Eventually, with free online math help and live tutors you make sense of algebra, geometry, trigonometry and the rest of it. Work with online tutors everyday for a little while, and your math grades will soon take an upward curve.

Step 1:

Factorized polynomials

125 - 5x^{2} = 5(25 - x^{2} )

= 5(5^{2} - x^{2} )

= 5(5 - x)(5 + x) [a^{2} - b^{2} = (a - b)(a + b)]

and

x^{2} + 3x - 10 = x^{2} + 5x - 2x - 10

= x(x + 5) - 2(x + 5)

= (x - 2)(x + 5)

Step 2:

125 - 5x^{2} = 5(5 - x)(5 + x)

x^{2} + 3x - 10 = (x - 2)(x + 5)

=> The required GCD = x + 5. answer

Factorized polynomials

125 - 5x

= 5(5

= 5(5 - x)(5 + x) [a

and

x

= x(x + 5) - 2(x + 5)

= (x - 2)(x + 5)

Step 2:

125 - 5x

x

=> The required GCD = x + 5. answer

$\frac{x^3 - 27}{5x^2 - 13x - 6}$

Step 1:

Factorized polynomials

x^{3} - 27 = x^{3} - 3^{3}

= (x - 3)(x^{2} + 3x + 9)

[a^{3} - b^{3} = (a - b)(a^{2} + ab + b^{2} )]

and

5x^{2} - 13x - 6 = 5x^{2} - 15x + 2x - 6

= 5x(x - 3) + 2(x - 3)

= (5x + 2)(x - 3)

Step 2:

$\frac{x^3 - 27}{5x^2 - 13x - 6}$ = $\frac{ (x - 3)(x^2 + 3x + 9)}{(5x + 2)(x - 3)}$

= $\frac{x^2 + 3x + 9}{5x + 2}$

=> $\frac{x^3 - 27}{5x^2 - 13x - 6}$ = $\frac{x^2 + 3x + 9}{5x + 2}$

Factorized polynomials

x

= (x - 3)(x

[a

and

5x

= 5x(x - 3) + 2(x - 3)

= (5x + 2)(x - 3)

Step 2:

$\frac{x^3 - 27}{5x^2 - 13x - 6}$ = $\frac{ (x - 3)(x^2 + 3x + 9)}{(5x + 2)(x - 3)}$

= $\frac{x^2 + 3x + 9}{5x + 2}$

=> $\frac{x^3 - 27}{5x^2 - 13x - 6}$ = $\frac{x^2 + 3x + 9}{5x + 2}$

Step 1:

Let the fraction is $\frac{x}{y}$

=> $\frac{x}{y}$ = $\frac{2}{3}$ ......................(1)

also given, when 5 is subtracted from the numerator and 3 added to the denominator, the ratio becomes 1:3.

=> $\frac{x - 5}{y + 3}$ = $\frac{1}{3}$ ........................(2)

Step 2:

(1) => x = $\frac{2}{3}$y ............................(3)

and (2) => 3(x - 5) = y + 3

=> 3x - 15 = y + 3

=> 3x - y = 18 ................................(4)

Step 3:

Put x = $\frac{2}{3}$y in equation (4)

=> 3 * $\frac{2}{3}$ y - y = 18

=> 2y - y = 18

=>** y = 18,** put in equation (3)

=> x = $\frac{2}{3}$ * 18

=>**x = 12**

Hence the numbers are** 12 and 18.**

Let the fraction is $\frac{x}{y}$

=> $\frac{x}{y}$ = $\frac{2}{3}$ ......................(1)

also given, when 5 is subtracted from the numerator and 3 added to the denominator, the ratio becomes 1:3.

=> $\frac{x - 5}{y + 3}$ = $\frac{1}{3}$ ........................(2)

Step 2:

(1) => x = $\frac{2}{3}$y ............................(3)

and (2) => 3(x - 5) = y + 3

=> 3x - 15 = y + 3

=> 3x - y = 18 ................................(4)

Step 3:

Put x = $\frac{2}{3}$y in equation (4)

=> 3 * $\frac{2}{3}$ y - y = 18

=> 2y - y = 18

=>

=> x = $\frac{2}{3}$ * 18

=>

Hence the numbers are